Bread and Wine - O'Neill, J. C. 1930-2003 (1995)
The Christian practice of meeting for worship and receiving token pieces of bread and token sips of wine seems unlikely to have had Jewish precedents. You don't eat in a synagogue; you eat at home. To be sure, specific acts of eating bread and drinking wine are given religious significance in the setting of the Passover meal, but that is not quite the same, although perhaps we might suppose the Christian practice to have evolved from the Jewish meal.